2022
DOI: 10.3390/nu14020398
|View full text |Cite
|
Sign up to set email alerts
|

Adansonia digitata L. (Baobab Fruit) Effect on Postprandial Glycemia in Healthy Adults: A Randomized Controlled Trial

Abstract: Baobab fruits have been traditionally used in Africa due to their therapeutic properties attributed to their high polyphenol content. The aim of the study was to investigate the effect of baobab fruit on postprandial glycaemia in healthy adults and to measure its bioactive compounds and antioxidant activity. The study (NCT05140629) was conducted on 31 healthy subjects. The participants were randomly allocated in the control group (oral glucose tolerance test (OGTT); n = 16) and in the intervention group (OGTT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…75 It has been demonstrated that tannins minimize the risk of developing diabetes by improving glucose absorption and lowering blood sugar levels. 76 Saponins enhance the activities of various antioxidant enzymes such as catalases and superoxide dismutase, which is usually lowered in hyperglycemic conditions. 77 The various plant extracts are cost-effective, safe, and environmentally benign for the creation of NPs, 78,79 So in the present project KE-AgNPs were successfully synthesized from KE extract via green processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 It has been demonstrated that tannins minimize the risk of developing diabetes by improving glucose absorption and lowering blood sugar levels. 76 Saponins enhance the activities of various antioxidant enzymes such as catalases and superoxide dismutase, which is usually lowered in hyperglycemic conditions. 77 The various plant extracts are cost-effective, safe, and environmentally benign for the creation of NPs, 78,79 So in the present project KE-AgNPs were successfully synthesized from KE extract via green processing.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of tannins derived from medicinal plants help to slow the onset of diabetes and its associated complications by acting on key biochemical pathways and targets 75 . It has been demonstrated that tannins minimize the risk of developing diabetes by improving glucose absorption and lowering blood sugar levels 76 . Saponins enhance the activities of various antioxidant enzymes such as catalases and superoxide dismutase, which is usually lowered in hyperglycemic conditions 77 …”
Section: Discussionmentioning
confidence: 99%
“…They increase glucose transporter isoform 2 (GLUT)2 expression in pancreatic -cells and stimulate GLUT4 translocation via the Phosphoinositide 3-kinases (PI3K)/Protein kinase B (Akt) and adenosine monophosphate (AMP-activated protein kinase pathways. Thus, glucose metabolism improved, notably with the BuOH fraction, which had antihyperglycemic/antihyperlipidemic characteristics and relieved streptozotocin-induced pancreatic damage [184] .…”
Section: Cardiovascular Health and Antidiabetic Benefits Of Usae Bioa...mentioning
confidence: 98%
“…The formation of reactive oxygen species (ROS) and cellular mitochondrial dysfunction happens due to the advanced glycation of proteins and lipids. As a result, these antioxidants help to prevent endothelial dysfunction [184] . anti-diabetic action includes Chlorogenic and ferulic acids; both stimulate transporters and have anti-diabetic properties.…”
Section: Cardiovascular Health and Antidiabetic Benefits Of Usae Bioa...mentioning
confidence: 99%
“…The po tential effect of this fruit in glycemia management has been attributed to procyanidin com pounds that activate insulin signaling pathways and glucose transport to the adipose and muscle cells [17]. Results from animal and human studies have shown Adansonia digitat L. fruit aqueous extract ingestion to be effective in blood glucose level control [18,19].…”
Section: Introductionmentioning
confidence: 99%